2014
DOI: 10.1063/1.4871092
|View full text |Cite
|
Sign up to set email alerts
|

Tunable effective nonlinear refractive index of graphene dispersions during the distortion of spatial self-phase modulation

Abstract: Spatial self-phase modulation (SSPM) was observed directly when a focused He-Ne laser beam at 633 nm went through liquid-phase-exfoliated graphene dispersions. The diffraction pattern of SSPM was found to be distorted rapidly right after the incident beam horizontally passing through the dispersions, while no distortion for the vertically incident geometry. We show that the distortion is originated mainly from the non-axis-symmetrical thermal convections of the graphene nanosheets induced by laser heating, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
71
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(81 citation statements)
references
References 30 publications
(45 reference statements)
2
71
0
1
Order By: Relevance
“…The mechanism of SSPM in the TMDs dispersions is the same as the situation in nematic liquid crystal films and graphene [9,17,18]. According to the optical Kerr effect, the effective refractive index of the TMDs dispersions can be described by [17] n e n 0e In 2e ;…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The mechanism of SSPM in the TMDs dispersions is the same as the situation in nematic liquid crystal films and graphene [9,17,18]. According to the optical Kerr effect, the effective refractive index of the TMDs dispersions can be described by [17] n e n 0e In 2e ;…”
mentioning
confidence: 92%
“…(4) and (5), N eff is the parameter that needs to be determined in order to estimate χ 3 monolayer . Following the case of graphene [18], N eff of the TMDs nanosheets can be estimated by T N eff monolayer T total , where T total is the transmittance of the three TMDs dispersions and T monolayer is the transmittance of a TMDs monolayer. T monolayer for the MoS 2 , WS 2 , and MoSe 2 monolayers was determined to be 99.4%, 99.70%, and 99.10%, respectively [6].…”
mentioning
confidence: 99%
“…For experimental investigation of NLO response, self-phase modulation29303132 and Z-scan measurement203334 are the most popular experimental methods, and we chose the latter. Significant saturable absorption was observed at all of the excitation wavelengths (532 nm, 800 nm, 1050 nm and 1550 nm), which indicated their ultra-broadband saturable absorption characteristics.…”
mentioning
confidence: 99%
“…H. Zhang et al showed that graphene possesses the giant nonlinear refractive index of n 2 10 −7 cm 2 W −1 , almost nine orders of magnitude larger than bulk dielectrics, using the Z-scan technique on loosely stacked few-layer graphene [12]. The spatial self-phase modulation was observed directly by G. Wang et al when a focused He-Ne laser beam at 633 nm went through liquid-phase-exfoliated graphene dispersions [13]. They estimated the relative change of effective nonlinear refractive index by tuning the incident intensity or the temperature of the dispersions.…”
mentioning
confidence: 99%